Performance of LHAASO-WCDA and observation of the Crab Nebula as a standard candle *Supported by the following grants: the National Key R&D program of China (2018YFA0404201, 2018YFA0404202, 2018YFA0404203), the National Natural Science Foundation of China (12022502, 11905227, U1931112, 11635011, 11761141001, Y811A35, 11675187, U1831208, U1931111) and in Thailand by RTA6280002 from Thailand Science Research and Innovation. (August 2021) - Aharonian, F.; An 安, Q. 琪; Axikegu 阿西, 克古; Bai 白, L.X. 立新; Bai 白, Y.X. 云翔; Bao 包, Y.W. 逸炜; Bastieri, D.; Bi 毕, X.J. 效军; Bi 毕, Y.J. 玉江; Cai 蔡, H. 浩; Cai 蔡, J.T. 金庭; Cao 曹, Z. 臻; et al.
Abstract: The first Water Cherenkov detector of the LHAASO experiment (WCDA-1) has been operating since April 2019. The data for the first year have been analyzed to test its performance by observing the Crab Nebula as a standard candle. The WCDA-1 achieves a sensitivity of 65 mCU per year, with a statistical threshold of 5 . To accomplish this, a 97.7% cosmic-ray background rejection rate around 1 TeV and 99.8% around 6 TeV with an approximate photon acceptance of 50% is achieved after applying an algorithm to separate gamma-induced showers. The angular resolution is measured using the Crab Nebula as a point source to be approximately 0.45° at 1 TeV and better than 0.2° above 6 TeV, with a pointing accuracy better than 0.05°. These values all match the design specifications. The energy resolution is found to be 33% for gamma rays around 6 TeV. The spectral energy distribution of the Crab Nebula in the range from 500 GeV to 15.8 TeV is measured and found to be in agreement with the results from other TeV gamma ray observatories.